Geomorphology and glacial history of Rauer Group, East Antarctica - White, DA; Bennike, O; Berg, S; Harley, SL; Fink, D; Kiernan, K; McConnell, A; Wagner, B (Quaternary Research, 2009)
The presence of glacial sediments across the Rauer Group indicates that the East Antarctic ice sheet formerly covered the entire archipelago and has since retreated at least 15 km from its maximum extent. The degree of weathering of these glacial sediments suggests that ice retreat from this maximum position occurred sometime during the latter half of the last glacial cycle. Following this phase of retreat, the ice sheet margin has not expanded more than 1 km seaward of its present position. This pattern of ice sheet change matches that recorded in Vestfold Hills, providing further evidence that the diminutive Marine Isotope Stage 2 ice sheet advance in the nearby Larsemann Hills may have been influenced by local factors rather than a regional ice-sheet response to climate and sea-level change.